Shoot induction and plant regeneration from cotyledon segments of the muskmelon variety "hógolyó" - Bársony, Cs.; Bisztray, Gy.; Bába, E.; Velich, E. (International Journal of Horticultural Science, 1999)
Cotyledonary segments of the casaba type muskmelon variety "Hógolyó" were used to induce organogenesis. Fifty different hormone combinations were applied to enhance the induction of shoot formation on the edge of the segments. The phases of organogenesis were followed with light- and scanning electron microscope. Shoot induction was achieved with high frequency. The shoots were transferred to hormone free media for root induction. The rooted plantlets were planted out to soil.NAA was feasible and the method can be applied in transformation experiments.